y = 3Cosx + 2Sin²x - 1
Найдём производную :
y' = (Cosx)' + 2(Sin²x)' - 1' = - 3Sinx + 4SinxCosx
Приравняем производную к нулю :
- 3Sinx + 4SinxCosx = 0
Sinx(- 3 + 4Cosx) = 0
Sinx = 0
- 3 + 4Cosx = 0
Cosx = 0,75
Если Sinx = 0 , то Cosx = ± 1
1) Sinx = 0 ⇒ Cosx = - 1 ⇒
y = 3 * (- 1) + 2 * 0 - 1 = - 4 - наименьшее
2) Sinx = 0 ⇒ Cosx = 1 ⇒
y = 3 * 1 + 2 * 0 - 1 = 2
3) Cosx = 0,75 ⇒ Sin²x = 1 - Cos²x = 1 - 0,75² = 1 - 0,5625 = 0,4375
y = 3 * 0,75 + 2 * 0,4375 - 1 = 2,25 + 0,875 - 1 = 2,125 - наибольшее
ответ : наименьшее - 4 , наибольшее 2,125
Поделитесь своими знаниями, ответьте на вопрос:
Х²-144=0 x²+25=0 x²-5=0 (x-1)²=9 (x+5)=0
х²-144=0
x²=144
x=±12
x²+25=0
x²=-25
x ∈ ∅⇒нет реш.
x²-5=0
x²=5
x=±√5
(x-1)²=9
x²-2x-8=0
d=36
x=-2
x=4